Role of FAK signaling in chagasic cardiac hypertrophy - Tucci,Amanda R. (2020)
Abstract Cardiac hypertrophy and dysfunction are a significant complication of chronic Chagas disease, with heart failure, stroke, and sudden death related to disease progression. Thus, understanding the signaling pathways involved in the chagasic cardiac hypertrophy may provide potential targets for pharmacological therapy. Herein, we investigated the implication of focal adhesion kinase (FAK) signaling pathway in triggering hypertrophic phenotype during acute and chronic T. cruzi infection. C57BL/6 mice infected with T. cruzi (Brazil strain) were evaluated for electrocardiographic (ECG) changes, plasma levels of endothelin-1 (ET-1) and activation of signaling pathways involved in cardiac hypertrophy, including FAK and ERK1/2, as well as expression of hypertrophy marker and components of the extracellular matrix in the different stages of T. cruzi infection (60–210 dpi). Heart dysfunction, evidenced by prolonged PR interval and decrease in heart rates in ECG tracing, was associated with high plasma ET-1 level, extracellular matrix remodeling and FAK signaling activation. Upregulation of both FAK tyrosine 397 (FAK-Y397) and serine 910 (FAK-S910) residues phosphorylation as well as ERK1/2 activation, lead to an enhancement of atrial natriuretic peptide gene expression in chronic infection. Our findings highlight FAK-ERK1/2 signaling as a regulator of cardiac hypertrophy in Trypanosoma cruzi infection. Both mechanical stress, induced by cardiac extracellular matrix (ECM) augment and cardiac overload, and ET-1 stimuli orchestrated FAK signaling activation with subsequent activation of the fetal cardiac gene program in the chronic phase of infection, highlighting FAK as an attractive target for Chagas disease therapy.